Inheritance of a sign of apricot color of ray flowers of sunflower (Helianthus annuus L.) - К. В. Ведмедєва (Plant Varieties Studying and Protection)
Purpose. To reveal the nature of the inheritance of apricot color of the ray flowers of the sunflower and the type of interaction of genes causing different colors. Methods. Field experiment, genetic analysis. The statistical validity of the results was evaluated using Pearson’s criterion. Results. We conducted crosses of the ‘KG13’ line as the source of the sign of apricot color with sunflower lines that had yellow, orange and lemon colors of the ray flowers. In the first generation, from crossing the ‘KG13’ line with five lines, which had a yellow color, only a yellow color of ray flowers was observed. In the second generation, a 3 : 1 split was observed: three-quarters with yellow flowers and one with apricot flowers. Line ‘KG13’ was crossed with three lines (‘HA298’, ‘SL2966’, ‘LD72/3’), which had an orange color of flowers. In the first generation, orange flowers were observed; in the second generation, splitting was recorded: three-quarters of offsprings with orange-colored flowers and one-quarter with apricot flowers. The line ‘KG13’ was crossed with ‘KG107’ and ‘ZL678’, which had lemon-colored flowers. The resulting plants of the first generation had a yellow coloration of ray flowers. In the second generation, five classes of plants by coloration of ray flowers were obtained: yellow, orange, apricot, lemon, lemon-apricot in the ratio 6 : 4 : 3 : 2 : 1. According to these data, the genes of lemon and apricot color have a complementary effect, the homozygous state of orange allele is epistatic to the recessive homozygote of the lemon-colored gene. The ‘KG108’ line with a combination of genes responsible for apricot and light yellow color has its own light apricot color and in crossings with a yellow colored line in the second generation gives splitting in the ratio 9 : 3 : 3 : 1. Conclusions. It was revealed that the apricot color of the ray flowers of the sunflower line ‘KG13’ is due to the homozygous state of the allele of the same gene whose second allele causes an orange color in the lines ‘NA298’, ‘SL2966’ and ‘LD72/3’. The complementary action of alleles responsible for apricot and lemon, as well as apricot and light yellow coloration of ray flowers was determined. A case of epistasis of homozygotes along the allele controlling the orange color over the recessive homozygote of the gene, which is controlled by the lemon color in the crossing combination ‘ZL678’ / ‘KG13’, was revealed.